2020
DOI: 10.3390/rs12142195
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spatial Limits of Sentinel-2 Data on Arable Crops in the Context of Checks by Monitoring

Abstract: The availability of large amounts of Sentinel-2 data has been a trigger for its increasing exploitation in various types of applications. It is, therefore, of importance to understand the limits above which these data still guarantee a meaningful outcome. This paper proposes a new method to quantify and specify restrictions of the Sentinel-2 imagery in the context of checks by monitoring, a newly introduced control approach within the European Common Agriculture Policy framework. The method consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…This was due to the proximity of trees from different species, sometimes less than two meters, but also due to the spatial autocorrelation of the pixels. Each pixel influences its neighborhood [42], reducing the effective pixel resolution. It is worth mentioning that the spatial miss-registration in the Sentinel-2 images series vary by around 12 m (more than one pixel) but can be greater than 3 pixels according to [43].…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…This was due to the proximity of trees from different species, sometimes less than two meters, but also due to the spatial autocorrelation of the pixels. Each pixel influences its neighborhood [42], reducing the effective pixel resolution. It is worth mentioning that the spatial miss-registration in the Sentinel-2 images series vary by around 12 m (more than one pixel) but can be greater than 3 pixels according to [43].…”
Section: Remote Sensing Datamentioning
confidence: 99%
“…The proposed methodology is an accurate and efficient alternative to generate land abandonment maps since it allows obtaining maps with high accuracy from a reduced set of training data. In addition, the limitations of Sentinel-2 for areas with high spatial fragmentation was overcome thanks to the use of VHR images [16][17][18]. We created a complete map of abandoned citrus plots in the Oliva municipality for the year 2019, that detected a 31% of erroneously classified plots in the current methodology used by the public administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on citrus already showed serious discrepancies between agriculture census data and satellite-derived cropland area using medium-resolution satellite imagery as Landsat [13]. Sentinel-2 images overcome some of these limitations and showed its potential in agricultural applications [14,15], however in areas with high spatial fragmentation they may be not enough [16,17]. The Sentinel-2 satellite images did not show enough accuracy to identify abandoned plots in our study area due to resolution limitations and the small size of the plots, for this reason, the use of higher resolution images is recommended [18].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, it might also mitigate the negative effect of the imperfect geometric accuracy of the image. As was suggested in [44] in the context of a Sentinel-2 analysis, a buffer size of −5 m is chosen in the present study. Another possible source of noise is the fact that the edges of the fields are sometimes managed differently from the central part of the fields (different machines passage orientation or inputs interdiction for example), which causes heterogeneity in the parcel signal.…”
Section: Parameters and Scenariosmentioning
confidence: 99%